Pertumbuhan dan Alokasi Biomassa Organ Tanaman Mahoni (Swietenia mahagoni L.) yang Ditanam Pada Tanah Bekas Tambang Emas dengan Perlakuan Pupuk Kandang - Ambardini, Sri; Ningsih, Rita; Kali, Yustina Rante (Fakultas MIPA UNM, 2018)
Abstract. Â The purpose of this study is to determine the growth and biomass allocation of Mahagony plant organs are planted on ex-gold mining soil with manure treatment. The experimental research with four treatments are control (without manure), manure (cow, goat, chicken) with five replications. The plant growth parameters are observed consist of plant height, stem diameter, leaf number, leaf area, rooth lenght, dry weight, and biomass percentage are located to leaves, stems and plant roots. The data are tested anova and continue with t-test. The result showed that the treatment of manure had efeect on the growth and mahagony planted on ex-golg mining soil. Plant biomass on all manure treatment are largest alloccated to leaves organ then to stems and roots. Based on t-test result that the cow manure treatment is better to supporting growth and biomass of mahagony plant than chicken manure, goat manure and control.Keywords: growth, biomass, mahagony, ex-gold mining soil, manure